Pattern of organizational entrepreneurship development in heritage, handicrafts, and tourism organization - Homayoun Yousefi, Dr. Seyed Saeed Hashemi, (Opción)
The objective of this research is to provide a Pattern of organizational entrepreneurship development in the tourism field in the cultural heritage, handicrafts, and tourism organization. Data collection tool in the qualitative step is the semi-structured and open interviews. Research results show that cultural heritage, handicrafts, and tourism organization need a realistic and long-term approach, and partial, short-term, and sectional approaches will not be useful. In conclusion, the entrepreneurial activities of the organization members must be improved to have the dynamic organization that the role of the organization managers in growing the entrepreneurship is so vital.